Arrangement Strategy of Corridor Madukoro to Support Semarang Urban Tourism - Rachmayanie, Arieska Avianda; Sari, Suzanna Ratih; Rukayah, R. Siti (Universitas Negeri Semarang, 2023)
One of Semarang government’s efforts to support urban tourism is airport development. It affects changes in access to and from Ahmad Yani Airport. Madukoro corridor is a priority because it is the first corridor through which migrants from outside Semarang come by air. However, there are issues related to urban tourism in Madukoro corridor, elements that are currently not optimal in supporting tourism activities in Semarang, especially those located around the PRPP destinations, Grand Maerakaca, and Kampung Laut. This study aims to find the most optimal structuring strategy in Madukoro corridor to better support urban tourism in Semarang on the coast, without neglecting its ecological conditions. To be able to explore the potential and identify problems that exist in Madukoro corridor, this research was carried out using a mixed-method in the form of a qualitative method that was quantified by weighing and rating. The study was conducted using a SWOT analysis equipped with a SWOT matrix to determine the most appropriate strategy. This research is also equipped with a strategic analysis of internal factors (IFAS) and external factors (EFAS) so that the score values can be converted on a quadrant graph to determine the type of strategy that should be used. From the results of the SWOT analysis, to develop urban tourism the strategy taken is progressive, prioritizing according to Weakness-Opportunity strategies, with implications for the physical development of city infrastructure, utilization of commercial buildings in the surrounding area, ease of accessibility to Grand Maerakaca, and Kampung Laut as well as improving the quality of the Nodes that affect the spatial pattern of regional circulation and regional landmark.